A compact multiband planar monopole antenna for slim mobile handset applications - Bharti P.K.; Pandey G.K.; Singh H.S.; Meshram M.K. (My University, 2025)
A planar compact multiband monopole antenna is presented for ultra-slim mobile handset applications. The proposed antenna operates over 0.885 GHz-0.962 GHz and 1.69 GHz-3.8GHz frequency bands with -6 dB impedance bandwidth that covers GSM900, GSM1800, GSM1900, UMTS, IMT2100, WLAN, WiMAX along with most of the higher LTE bands of modern mobile phone applications. The radiation characteristics of the antenna is analyzed in term of radiation patterns, peak realized gain, total radiation efficiency, and surface current distribution. The radiation patterns of the proposed antenna are dipole like which is suitable for mobile applications with 73-93% total radiation efficiency. The proposed antenna is investigated in free space as well as in actual mobile environment consisting of mobile plastic housing along with large metallic display screen and battery. No significant effect on the operating bands of the mobile antenna due to the actual mobile environment on the impedance bandwidth is observed. Specific absorption rate (SAR) computation is carried out on human head phantom. The computed values of SAR lie well below the specified limit over 1 g and 10 g of tissues. The parametric analysis is also carried out to understand the effect of the shape parameters.